Even when those struggles are not our own: Storytelling and solidarity in a feminist social justice organization. Issue 4 (11th July 2019) - Weatherall, Ruth
Abstract : This article draws on an eight‐month ethnography in a feminist social justice organization that supports survivors of domestic violence and shares the storytelling practices that fostered solidarity. These storytelling practices stemmed from decades of decolonizing work undertaken by Māori women to have their knowledge and ways of being equally integrated into the organization. The storytelling practices, grounded in Māori knowledge, emphasized that the land is actively productive of our identity and knowledge; our actions and beliefs are part of a non‐chronological intergenerational inheritance; the personal is collective. I contend that these practices fostered solidarity and situated feminism in a collective history of localized struggle. Accordingly, this article expands our imaginative capacity for how solidarity can be thought of and fostered between feminists in different contexts.